Park guiding in National Parks using thematic interpretation for conservation – the Chief Minister’s outstanding park guiding award - Chan, Margaret Kit Yok (UiTM Sarawak, 2016)
The strategic roles of thematic interpretation in visitor management of national parks and in the context of tourism as a positive force for conservation and sustainable development are widely acknowledged as a necessary centerpiece of conservation and sustainable tourism. The approach is known to have the potential to influence visitors' beliefs and actions toward the natural and cultural resources, and because of its importance in positively shaping both the nature and quality of visitor experiences.